Antibiotic Resistance in Czech Urban Wastewater Treatment Plants: Microbial and Molecular Genetic Characterization - Svobodová, Kateřina; Semerád, Jaroslav; Petráčková, Denisa; Novotný, Čeněk (Microbial drug resistance (Larchmont, N.Y.), 2018)
Quantitative changes in antibiotic resistance genes (ARGs) were investigated in six urban wastewater treatment plants (WWTPs) treating municipal and industrial wastewaters. In a selected WWTP, the fate of ARGs was studied in a 1-year time interval and in two phases of wastewater treatment process. Nine ARGs (tetW, tetO, tetA, tetB, tetM, blaTEM, ermB, sul1, and intl1) were quantified in total and their relative abundance assessed by ARG copies/16SrRNA copies. From the tetracycline resistance genes, tetW was the only one detected in all sampled WWTPs. Its relative abundance in the nitrification tank of WWTP5 was found stable during the 1-year period, but was lowered by secondary sedimentation processes in the wastewater treatment down to 24% compared to the nitrification tank. Bacterial isolates showing high tetracycline resistance (minimal inhibition concentrations >100 μg/mL) were identified as members of Acinetobacter, Klebsiella, Citrobacter, Bacillus, and Enterobacter genera. Dynamic shifts in the relative abundance of ermB and sul1 were also demonstrated in wastewater samples from WWTP5.
Keywords: resistome; Genes, Bacterial; Environmental Monitoring; tetracycline; Tetracycline; RNA ribozomální 16S; rezistence na tetracyklin; antibiotic resistance genes; wastewater treatment plants; RNA, Ribosomal, 16S; Wastewater; monitorování životního prostředí; Waste Water; bakteriální geny; Czech Republic; tetracyklin; odpadní voda; Bacteria; Česká republika; Tetracycline Resistance